CHANGING THE TRAJECTORY OF GROWTH: THE APPLICATION OF VOSORITIDE IN CHILDREN WITH ACHONDROPLASIA. A CHANCE FOR IMPROVED QUALITY OF LIFE? - Marta Turek; Julia Szlążek; Michalina Zagalska; Adam Jan Ząbek; Kamil Kerknawi; Paulina Mikulec; Marceli Mesyasz; Tomasz Tamborski; Jakub Paweł Kuźniar; Emilia Gabriela Chrzanowska (International Journal of Innovative Technologies in Social Science, 2025)
Achondroplasia (ACH) is the most common skeletal dysplasia and the leading genetic cause of dwarfism. It is characterized by disproportionate short stature and lifelong medical complications, with an estimated incidence of 1 in 25,000–30,000 live births. The condition results from a mutation in the fibroblast growth factor receptor 3 (FGFR3) gene, causing receptor overactivation and impaired bone growth at the growth plates. This review provides an overview of achondroplasia, including its pathophysiology, clinical features, diagnostic methods, and novel therapeutic options, with emphasis on vosoritide. Historically, management has focused on symptomatic treatment and surgical interventions to address complications such as foramen magnum stenosis, hydrocephalus, and postural deformities. Vosoritide (Voxzogo) marks a breakthrough as the first disease-modifying therapy targeting the underlying pathophysiology. It is a C-type natriuretic peptide (CNP) analog that inhibits the overactive MAPK pathway, thereby promoting chondrocyte proliferation and differentiation in growth plates and enabling endochondral bone growth. Phase 3 clinical trials demonstrated that vosoritide significantly increases annual growth velocity (by approximately 1.57 cm) and improves body proportions, with a favorable safety profile. Reported adverse effects were generally mild, including transient hypotension and injection site reactions. Despite these advances, vosoritide therapy does not eliminate the need for coordinated multidisciplinary care and psychological support. Patients require ongoing monitoring and management of associated complications, including neurological, orthopedic, respiratory, and developmental issues. In summary, achondroplasia remains the most frequent genetic form of dwarfism, traditionally managed through supportive care and surgery. The introduction of vosoritide represents a paradigm shift, offering the first targeted therapy that directly modifies disease progression and opens new perspectives for improving patients’ quality of life.